Does redistribution hurt growth? An Empirical Assessment of the Redistribution-Growth Relationship in the European Union - Michael Christl; Silvia De Poli; Monika Köppl-Turyna (Global Labor Organization (GLO), 2024)
This paper analyzes the relationship between economic growth, inequality and redistribution. In a cross-country setting for 25 EU countries over the period 2007-2019, we show that market income inequality is associated with higher growth in the short run. To estimate the impact of redistribution to low-income earners, we introduce a new measure, the so-called net benefit share (NBS). Contrary to other findings, we show that this (targeted) redistribution to lowincome earners (Q1 NBS) boosts growth in the short run, driven by the consumption and private investment channels. On the other hand, untargeted redistribution to higher income earners reduces growth.
Keywords: H23; O47; D63; 330; growth; redistribution; inequality; European Union